2020
DOI: 10.3389/fvets.2020.00436
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reduced Dietary Crude Protein in the Starter Phase on Immune Development and Response of Broilers Throughout the Growth Period

Abstract: Crude protein (CP) levels in commercial broiler (Gallus gallus) diets, optimized for maximum yield production vs. feed cost, have only begun to be assessed for impact on immune function. In order to study immune effects of dietary CP levels, different starter phase (day 1-14) diets were fed to 230 Ross 708 male broiler chicks randomly assigned at 1 day of age into two treatment groups. Group 1: Standard diet (STD) contained 3,000 kcal AMEn/kg energy and 23.78% CP; and Group 2: Reduced crude protein diet (RCP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This present finding is in agreement with the reports of previous researchers [18,27,31,32] who confirmed that maintaining a minimum level of 2.32% in diets via Gly supplementation allowed to decreased dietary CP concentration up to 3% or more without compromising the accumulative growth performance of broiler chickens (1-21 d old). Also, our result is in accordance with previous reports which suggested that maintenance of optimal amino acid ratios for essential amino acids and sufficient total Gly + Ser levels appear most important considerations in formulating broiler diets with reduced CP concentrations [2,25,[33][34][35]. According to Kamely et al [36], feeding low protein diets formulated to provide higher Gly + Ser and meet digestible amino acid requirements could be an efficient way to reduce nitrogen excretion to the environment and decrease feed cost without impacting growth performance.…”
Section: Tablesupporting
confidence: 93%
“…This present finding is in agreement with the reports of previous researchers [18,27,31,32] who confirmed that maintaining a minimum level of 2.32% in diets via Gly supplementation allowed to decreased dietary CP concentration up to 3% or more without compromising the accumulative growth performance of broiler chickens (1-21 d old). Also, our result is in accordance with previous reports which suggested that maintenance of optimal amino acid ratios for essential amino acids and sufficient total Gly + Ser levels appear most important considerations in formulating broiler diets with reduced CP concentrations [2,25,[33][34][35]. According to Kamely et al [36], feeding low protein diets formulated to provide higher Gly + Ser and meet digestible amino acid requirements could be an efficient way to reduce nitrogen excretion to the environment and decrease feed cost without impacting growth performance.…”
Section: Tablesupporting
confidence: 93%
“…It is worth noting that Kamely et al ( 44 ) reported no differences in inflammatory cytokine TNF-α and IL-1β expression in the abdominal cavity exudate of Ross 708 broilers. The discrepancy between the present study and Kamely et al ( 44 ) suggests that a low protein diet might affect the inflammatory system in a tissue-specific manner [systemic in our experimental conditions vs. local or abdominal cavity in Kamely et al ( 44 )]. The difference in the experimental approaches (diet formulation, amino acid levels, etc.)…”
Section: Discussionmentioning
confidence: 92%
“…Even under conditions of dietary deficiency for key substrate AA, prioritization of immune molecules synthesis can take priority over growth, as has been shown for prioritization of Arg for nitric oxide production in Eimeria -infected birds fed Arg deficient diets ( Rochell et al, 2017b ). Nonetheless, impaired immune response and increased disease susceptibility can occur when birds are fed reduced protein diets with unbalanced AA profiles ( Grimble and Grimble, 1998 ; Li et al, 2007 ; Kamely et al, 2020 ).…”
Section: Physiological Morphological and Metabolic Changes Following ...mentioning
confidence: 99%